Optimalisasi Pendidikan Kesehatan Gizi Terhadap Pencegahan Anemia pada Remaja melalui Permainan Ular Tangga Gizi Seimbang - Simbolon, Hot Marsitta Angelica; Linda Amalia; Upik Rahmi (Forum Kerjasama Pendidikan Tinggi, 2025)
Anemia or often called a condition caused by lack of blood where this disease is caused by iron deficiency, a type of micronutrient deficiency that is most common in the world. One of the individuals who are susceptible to anemia is adolescents who are influenced by several factors, namely age, knowledge or education, nutritional status, behavior, and consuming nutrition. Adolescence is one of the periods with a high chance of iron deficiency because there are many factors. The working area of ??the Dago Health Center in Bandung City in 2024 was identified as one of the health centers with the highest number of cases of adolescent anemia. Based on the results of the initial survey, it was found that SMP Pasundan 3 was the school and research location with the highest prevalence of adolescent anemia among schools in the area. This study aims to identify the effect of nutritional health education delivered through the balanced nutrition snakes and ladders game on preventing anemia in adolescents. This research method is a quasi-experimental with a pre-test post-test design with adolescent participants where the group of adolescents with anemia was selected as the research subjects. The study population of 40 adolescents at SMP Pasundan 3, each consisting of female and male adolescents with anemia. The results of the study showed that there was a significant difference between the two groups in the pre-test and post-test scores which showed (P<0.001). The intervention group consistently showed a higher mean score on both measurements indicating that the intervention was successful.